Substitution of all-purpose flour with sago (Metroxylon sagu Rottb.) flour in commercial shrimp cracker processing - Contreras-Aparente, Rhea Ann (2011)
This study was done to develop shrimp crackers that would utilize sago starch and shrimp head and shell for lower processing cost. Three formulations of sago and all-purpose flour with 10:90, 30:70 and 50:50 proportions were subjected to Preference Ranking Test. The data of this test were analyzed using Friedman's test and results showed that there was no significant difference among the three formulations. Hence, the 50:50 formulation was used as the final product formulation since the use of sago flour is maximized. This final product was then subjected to Consumer Acceptability test by 9-point Hedonic scale to determine the consumer's degree of liking to the product. The data was analyzed by computing the mode of the panelists' responses on the sensory attributes being tested: overall quality, appearance, flavour, and texture (crispiness). Results showed that most of the consumers liked the product very much. The chemical composition of the product was determined using AOAC Methods. The product consists of 31.96% carbohydrates, 48.86% protein, 11.98% moisture, 3.44% fat. 3.06% ash, 0.70% fiber and trace amounts of histamine. This product is tasty and light and can be consumed as snack and as side dish in a main course recipe.